Verification of utilities equipment accuracy for locating electric cable in complex installation / Muhammad Imran Shariffudin - Shariffudin, Muhammad Imran (2024)
Urban areas face significant challenges in maintaining and developing subsurface utility infrastructure due to the increasing complexity and density of underground utilities. The accurate detection and mapping of these utilities are crucial for ensuring efficient and safe urban development. This study aims to evaluate the accuracy and reliability of Ground Penetrating Radar (GPR) and Electromagnetic Locator (EML) technologies in detecting underground electric cables. The objectives include assessing the performance of different EML methods (induction and direct connection) and the effectiveness of GPR in achieving high precision in subsurface utility mapping. The research was conducted at UiTM Arau, Perlis, across two designated sites: a Real site and a Simulation site. The study employed EML methods (both induction and direct connection) to detect electric cables and GPR operating at an 800 Hz frequency to gather subsurface data. Data processing was conducted using Reflexw software, and accuracy was assessed using Root Mean Square Error (RMSE) calculations. The EML methods were evaluated for their RMSE values, with a particular focus on the impact of mutual coupling effects on accuracy. The study found that the direct connection method for EML demonstrated higher accuracy with lower RMSE values compared to the induction method, which was significantly affected by mutual coupling effects. The RMSE values for the induction method (2.56 for 8K Hz and 2.13 for 33K Hz) exceeded the acceptable threshold for Level A measurement accuracy as per JUPEM 2006 KPUP Circular 1. The GPR method showed high accuracy, with RMSE values within the acceptable range, supporting its effectiveness for precise underground utility detection. The results indicate that while GPR and the direct connection method of EML are suitable for achieving high precision in subsurface utility mapping, the induction method's susceptibility to mutual coupling effects limits its reliability. The RMSE value obtained for GPR on real site are 0.03 for cable 1, 0.03 for cable 2, 0.06 for cable 3 and cable 4 while for simulation 0.05 for both cable (cable 1 and cable 2). RMSE value obtain for EML instrument on real site are 4 m for induction method and 0.22 cm for direct connection method while on simulation site are 6 m for induction method and 0.09 cm for direct connection method. This study provides valuable insights for improving detection methods and supports the need for continued innovation in subsurface utility engineering.